On Leibniz algebras, whose subideals are ideals - Kurdachenko, L.A.; Subbotin, I.Ya.; Yashchuk, V.S. (Доповіді НАН України, 2017)
We obtain a description of solvable Leibniz algebras, whose subideals are ideals. A description of certain types of Leibniz T-algebras is also obtained. In particular, it is established that the structure of Leibniz T-algebras essentially depends on the structure of its nil-radical. Отримано опис розв'язних алгебр Лейбніца, всі підідеали яких є ідеалами. Наведено теореми, що дають опис деяких типів T-алгебр Лейбніца. Зокрема, структура T-алгебр Лейбніца істотно залежить від структури її ніль-радикала. Получено описание разрешимых алгебр Лейбница, все подидеалы которых являются идеалами. Приведены теоремы, которые дают описание некоторых типов T-алгебр Лейбница. В частности, структура T-алгебр Лейбница существенно зависит от структуры ее ниль-радикала.